PENGARUH PENGGUNAAN CHAT GPT TERHADAP POLA PIKIR MAHASISWA DALAM MATA KULIAH METODOLOGI PENELITIAN: STUDI PENELITIAN KUANTITATIF - Syahri, Anitia; Efriyanti, Liza; Zakir, Supratman; Imamuddin, M. (Information Technology Education Department, 2024)
This study aims to determine the effect of using Chat GPT on students' mindset in the Research Methodology course of the Informatics and Computer Engineering Education Study Program (PTIK) at State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi. This type of research is quantitative research with correlation method. The population in this study were 5th semester students in the Research Methodology course of the PTIK Study Program. The sample in this study were all 5th semester students in the PTIK Study Program Research Methodology course. The instrument used is a questionnaire on the use of Chat GPT and a questionnaire on the mindset obtained from these students. Based on the results of the study, the regression equation between the use of Chat GPT on the mindset of students is y = 139.627+1.137X. The correlation coefficient (rxy) value is 0.92 and the coefficient of determination (KD) value is 84.65%. From these results, it can be concluded that there is an effect of using Chat GPT on the mindset of students in the Research Methodology course of the PTIK Study Program at UIN Sjech M. Djamil Djambek Bukittinggi.